Correlation Between Soil Nitrogen Content and NDVI Derived from Sentinel-2A Satellite Imagery - Ni Made Trigunasih; Moh Saifulloh (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
The United Nations Educational, Scientific, and Cultural Organization (UNESCO) has recognized the Balinese agricultural irrigation system known as subak as part of the world's cultural heritage. Subak is the driver of Bali’s agricultural and tourism sectors and, therefore, must be preserved. Population growth triggers the conversions of land functions, from subak to built-up lands, such as those transpiring in Denpasar City. On the other hand, with the population continuously increasing, the demand for food becomes inevitably higher. This has caused farmers to intensify their agricultural practices through, for instance, applying chemical fertilizers excessively-potentially decreasing soil fertility. An example is urea fertilizer that contains a macronutrient, i.e., nitrogen (N). This study aimed to analyze the soil N content and its correlation with rice growth using the Normalized Difference Vegetation Index (NDVI). The Kjeldahl method was conducted to measure the N levels in the soil laboratory. NDVI was extracted from remote sensing data, namely Sentinel-2A imagery, on a cloud computing platform, Google Earth Engine (GEE), using Band 8 (NIR) with a wavelength of 0.842 m and Band 4 (Red) with 0.665 m. The results showed that the N levels varied from 0.09% to 0.31% and the average NDVI values ranged from 0.47 to 0.54. There is a strong correlation (r = 0.75 to 0.78) between the NDVI values derived from the Sentinel-2A Satellite Imagery and the soil nitrogen content. Spatially, based on the analysis results of the 2019‒2021 data, parts of existing subak systems, i.e., Subak Kerdung, Mergaya, Padanggalak, and Sembung, have high soil N contents and NDVI values.